Engineering the anthocyanin regulatory complex of strawberry (Fragaria vesca) - Lin-Wang, Kui; McGhie, Tony K.; Wang, Mindy; Liu, Yuhui; Warren, Benjamin; Storey, Roy; Espley, Richard V.; Allan, Andrew C. (Frontiers in Plant Science, 2014)
The woodland strawberry, Fragaria vesca is a model fruit for a number of rosaceous crops. We have engineered altered concentrations of anthocyanin in F. vesca, to determine the impact on plant growth and fruit quality. Anthocyanin concentrations were significantly increased by over-expression or decreased by knock-down of the R2R3 MYB activator, MYB10. In contrast, a potential bHLH partner for MYB10 (bHLH33) did not affect the anthocyanin pathway when knocked down using RNAi constructs. Metabolic analysis of fruits revealed that, of all the polyphenolics surveyed, only cyanidin and pelargonidin glucoside, and coumaryl hexose were significantly affected by over-expression and knock down of MYB10. Using the F. vesca genome sequence, members of the MYB, bHLH and WD40 families were examined. Global analysis of gene expression and targeted qPCR analysis of biosynthetic genes and regulators confirmed the effects of altering MYB10 expression, as well as the knock-down of bHLH33. Other members of the MYB transcription factor family were affected by the transgenes. Transient expression of strawberry genes in Nicotiana benthamiana revealed that MYB10 can auto-regulate itself, and potential repressors of MYB10. In tobacco, MYB10’s activation of biosynthetic steps is inhibited by the strawberry repressor MYB1.